Consumers’ Response to Socially Responsible Actions of Corporate: An Experimental Study - Anand, Ila Mehrotra; Oberai, Himani (International Journal of Psychosocial Rehabilitation, 2020)
Corporate social responsibility has become the buzz-word these days. It has drawn serious attention of the corporate across the globe. In this paper we aim to investigate the type of emotional response that gets generated when an individual is exposed to socially responsible actions of the corporate. Scenario based experimental design was used to manipulate the emotions. Respondents were assigned to the experimental as well as control condition using random sampling. PLS based SEM was used for the purpose of data analyses.